Lifting accessible model structures. Issue 1 (16th August 2019) - Garner, Richard; Kędziorek, Magdalena; Riehl, Emily
Abstract: A Quillen model structure is presented by an interacting pair of weak factorization systems. We prove that in the world of locally presentable categories, any weak factorization system with accessible functorial factorizations can be lifted along either a left or a right adjoint. It follows that accessible model structures on locally presentable categories – ones admitting accessible functorial factorizations, a class that includes all combinatorial model structures but others besides – can be lifted along either a left or a right adjoint if and only if an essential 'acyclicity' condition holds. A similar result was claimed in a paper of Hess–Kędziorek–Riehl–Shipley, but the proof given there was incorrect. In this note, we explain this error and give a correction, and also provide a new statement and a different proof of the theorem which is more tractable for homotopy‐theoretic applications.